Sistem Monitoring Ketinggian Air, Debit Air, Curah Hujan pada Sungai Berbasis IoT - Istiqomah, Ghina; Yuliatmojo, Pitoyo; Yusro, Muhammad (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2022)
The purpose of this research is to create an IoT-based monitoring system for water level, water discharge and rainfall on rivers, to make it easier for users to get information so that they are always ready if the air starts to rise in the rainy season. In developing research on water level monitoring systems, water discharge and rainfall on IoT-based rivers, researchers used the Research & Development Borg & Gall method. The results of the study indicate that the monitoring system can function properly and is in accordance with the objectives that have been designed by the researcher. The system is designed to use a water level sensor to measure the water level, a water flow sensor to measure water flow and a rain gauge sensor to measure rainfall. For output using LCD, lamp and buzzer. The monitoring tool has also been integrated by Telegram. The results for the water level get a range of 25 cm until 125 cm, for the speed of water discharge it gets a range of 10 until 40 mL/s and for rainfall, it gets a range of 1346 until 20193 mm/h.